Kallmann Syndrome Due to Heterozygous Mutation in SOX10 Coexisting With Waardenburg Syndrome Type II: Case Report and Review of Literature - Chen, Kan; Wang, Haoyu; Lai, Yaxin (Frontiers in Endocrinology, 2021)
Abstract Introduction: Kallmann syndrome (KS) is idiopathic hypogonadotropic hypogonadism with olfactory loss or decline. Waardenburg syndrome type Ⅱ (WS2) is a clinically and genetically heterogeneous disease, characterized by congenital sensorineural deafness and abnormal pigmentation of the iris, hair, and skin. Recently, mutations in the well-known WS pathogenic gene SOX10 have been found in some KS patients with deafness, but whether SOX10 is a co-pathogenic gene of KS and WS remains uncertain. Here, we report a rare case of KS and WS2 co-occurrence due to SOX10 mutations. Methods: Detailed histories were collected through questionnaires and physical examination. Blood samples of the patient and his family members were collected after obtaining informed consents. Suspected mutations were amplified and verified by Sanger sequencing after the next generation sequencing of related genes. The raw sequence data were compared to the knowe gene sequence data in publicly available sequence data bases using Burrows-Wheeler Aligner software (BWA, 0.7.12-r1039). Results: A 28-year-old male patient sought treatment for hypogonadism and the absence of secondary sexual characteristics. In addition, he showed signs of obesity, hyposmia, sensorineural hearing loss, and blue iris. Magnetic resonance imaging (MRI) of the olfactory bulb showed small bilateral olfactory bulbs and tracts and diaphragma Cerebri. MRI of the pituitary gland revealed a flat pituitary gland in the sella. Laboratory examination demonstrated hypogonadotropic hypogonadism, pituitary hypothyroidism, subclinical hypothyroidism, and the presence of insulin resistance with normal blood glucose levels. Sequencing of the SOX10 gene showed a 20 bp insertion in between coding bases 1179 and 1180 (c.1179_1180insACTATGGCTCAGCCTTCCCC). This results in a frame-shifting mutation of the 394th amino acid serine in exon4 with the resulting the amino acid sequence of the protein predicted to be TMAQPSP PSPAPSLTTL TISPQDPIMA TRARPLASTR PSPIWGPRSG PSTRPSLTPA PQGPSPTAPH TGSSQYIRHC PGPKGGPVAT TPRPAPAPSL CALFLAHLRP GGGSGGG*. Conclusion: SOX10 plays an important role in some critical stages of neural crest cell development and SOX10 mutation may be a common pathogenic factor for both KS and WS. Therefore, SOX10 mutation analysis should be considered for KS patients with combined WS clinical manifestations, especially deafness.